Automated Systems as a Part of Geotechnical Monitoring in Construction and Operation of Transport Tunnels. (2016) - Lebedev, Mikhail
Abstract: The safety of mining and tunneling operations considerably depends on availability of the most reliable and timely information on the stress-strain behavior of the "tunnel lining – containing rock massif" system and ground surface. Such information may be received by means of geotechnical monitoring using automated systems. The tasks to be solved as a part of the geotechnical monitoring are related to the assessment of the state of structural units to be built, containing rock massif, ground surface and buildings that fall within the construction-affected area. The need for preserving the buildings and facilities on ground surface gives the priority for the use of automated systems when determining the deformation of soil body starting from the outline of underground facilities and up to the ground surface. The obtained monitoring results allow, in the process of construction, making adjustments to the technological parameters of the mining and tunneling operations, to the parameters of the support setting and the tunnel lining construction technology, developing recommendations how to mitigate adverse effect on the environment. An example of the successful integration of the operational monitoring in an automated process control system is the tunnels of the Adler – Alpica Service section. There are 3 motor-road tunnels and 6 railroad tunnels in this section. During the construction, the lining of all tunnels was provided with control and measurement instrumentation to determine the stress-strain behavior of the "tunnel lining – containing rock massif" system and the seismic monitoring. The primary processing of the controlled parameters is done directly in the tunnels, then they are sent via a fiber-optic network to the geotechnical monitoring server located in the Operations Control Center. After the final processing, the data bank is updated. When the controlled parameters exceed the acceptable levels, an operator has the possibility to see, in the on-line mode, a specific location on the route, from where a signal is generated.